(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The origin of Geomorphology can be referred to 2500 years ago when the ancient Greek, Roman, Arab and Chinese philosophers tried to comprehend the occurrence of earthquakes, volcanoes and the presence of seashells at high mountains elevations. Leonardo da Vinci, during the Renaissance, discussed the formation of valleys based on observation of natural processes. After catastrophism and uniformitarianism theories as explanations of the origin of Earth’s relief, in the later part of the nineteenth century, geographical and geological surveys were carried out on the western United States giving important contributions to the development of geomorphological theory. Then, Davis, Penck, King had stated different models of landscape evolution. In the last few decades the Geomorphology has been dominated by the study of modern processes, their mechanics and rates of operations and on the behaviour of earth materials. In that sense, Alan Trenhaile has written Geomorphology: A Canadian Perspective, a comprehensive introduction to geomorphology, the study of physical features of the surface of the Earth and how they evolve. It is a text focused for undergraduate Geography and Earth Sciences Canadian students in its third edition